Improving Dental Hygiene Practices in Kindergarten Children: Teacher and Health Professional Involvement Initiative - Nadiah Thahirah AR (Wealth Community Empowerment, 2024)
Children are an age group prone to caries and other dental diseases, requiring help and guidance in maintaining oral and dental hygiene. Caries prevention activities are carried out through simple practices, such as brushing teeth, to improve understanding and practice of maintaining dental hygiene. This activity focuses on children in KB/TK PAPB Pedurungan Semarang. Activities involve counseling, demonstrations, and toothbrushing practices, involving family planning / kindergarten children, teachers, dentists, and oral dental therapists. The results of mentoring showed that children successfully applied the principle of brushing their teeth correctly, reflecting their understanding and ability to transfer knowledge to concrete actions. This activity not only provides information, but also builds children's intrinsic motivation in caring for their dental hygiene, with the result that children successfully apply the principle of brushing teeth correctly.